Analysis Factors Associated with Performance of Nusrses in RSUD Kota Depok, 2017 - Permatasari, P; Renata Febryani, D (KnE Life Sciences, 2018)
Nurses are the largest Human Resources (HR) that provide health services in hospital. Hospital nurses have an important role in the implementation of hospital functions to patients, therefore it requires a good performance so patients get the best service in achieving curative and rehabilitative goals. This study was conducted in RSUD Kota Depok between May and June 2017. Variables in this study are: (1) performance; (2) sex; (3) age; (4) education level; (5) years of service; (6) employment status; (7) work units; (8) work motivation; (9) work environment. This study is an analytical research with quantitative approach using cross-sectional study. The sample in this research is all of nurses in RSUD Kota Depok, the number is 79 nurses. Based on the results of this study, variables related to the performance of nurses in RSUD Kota Depok are job motivation (P = 0.011), work environment (P = 0.000) and work unit (P = 0.004), while gender (P = 0.113), age (P = 1.000), education level (P = 0.145), employment status (p = 0.823) and years of work (p = 0.312) are not related to nurse performance in RSUD Kota Depok 2017. Thus, it is expected that the management of RSUD Kota Depok considers factors related to the performance of nurses studied in this research, so that it is expected to measure the performance of nurses. Keywords: performance, work motivation, work environment, nurse performance, hospitals